Assessment of three root canal preparation techniques on root canal geometry using micro-computed tomography: In vitro study - Shaikha M Al-Ali; Musab H Saeed; Fawaz Almjali (Wolters Kluwer Medknow Publications, 2012)
Aim: To assess the effects of three root canal preparation techniques on canal volume and surface area using three-dimensionally reconstructed root canals in extracted human maxillary molars. Materials and Methods: Thirty extracted Human Maxillary Molars having three separate roots and similar root shape were randomly selected from a pool of extracted teeth for this study and stored in normal saline solution until used. A computed tomography scanner (Philips Brilliance CT 64-slice) was used to analyze root canals in extracted maxillary molars. Specimens were scanned before and after canals were prepared using stainless steel K-Files, Ni-Ti rotary ProTaper and rotary SafeSiders instruments. Differences in dentin volume removed, the surface area, the proportion of unchanged area and canal transportation were calculated using specially developed software. Results: Instrumentation of canals increased volume and surface area. Statistical analysis found a statistically significant difference among the 3 groups in total change in volume (P = 0.001) and total change in surface area (P = 0.13). Significant differences were found when testing both groups with group III (SafeSiders). Significant differences in change of volume were noted when grouping was made with respect to canal type (in MB and DB) (P < 0.05). Conclusion: The current study used computed tomography, an innovative and non destructive technique, to illustrate changes in canal geometry. Overall, there were few statistically significant differences between the three instrumentation techniques used. SafeSiders stainless steel 40/0.02 instruments exhibit a greater cutting efficiency on dentin than K-Files and ProTaper. CT is a new and valuable tool to study root canal geometry and changes after preparation in great details. Further studies with 3D-techniques are required to fully understand the biomechanical aspects of root canal preparation.